Promoting students’ sexual and reproductive health in peer-led programmes at two South African universities: Emergent tensions and dilemmas - van der Riet, M.; Akhurst, J.; Wilbraham, L. (South African Journal of Higher Education, 2019)
Sexual and reproductive health programmes with students in higher education in South Africa, are a neglected area of intervention. We report on piloting the peer-facilitated Auntie Stella intervention material at two South African universities. This participatory methodology encourages critical thinking by opening discussion on managing relationships, sexual decision-making, gender-based violence and risk-safety. The format involves various cards featuring a letter, a facilitated discussion, an answer-response and action points. Six focus groups of participants were facilitated by postgraduate students over four months. Using thematic analysis four tensions were identified in the student discussions: HIV awareness was in tension with relationship practices; awareness of risk was in tension with denial of vulnerability; awareness of individuals’ rights was in tension with claims on these rights; and HIV knowledge was in tension with HIV stigma. The Auntie Stella material has the potential to open up discursive spaces amongst students, and to develop agency in sexual decision-making.